Tragedy Illustration by Walter Molin - Kunto Adi Rumekso (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Walter Molino's creativity in producing illustrations rich in tragic themes has become unique among illustrators. His name has become legendary and an inspiration for many young illustrators who also explore similar themes. This article is a study of Walter Molino's illustrations through the Italian weekly newspaper La Domenica del Corriere. Walter Molino's genius in responding to issues in society and packaging them according to his own imagination and creativity without straying from the norms of the publishing world is a skill in itself, allowing all of this to continue to run smoothly. Molino's illustrations are known for their negative themes to most people, but there are many positive things that can be taken from his work and life process. One of them is how we can understand that success requires perseverance and authenticity.